METAPHORICAL AND METONYMIC FIGURATIVE MEANING AND THEIR RENDERING IN TRANSLATION (Spectrum Journal of Innovation, Reforms and Development, 2024)
Metaphorical and metonymic figurative meanings, their differences, rendering and translations in two languages are discussed.